Poor Things: Researching and the effects/affects on a (human) scale (Praxis Educativa, 2026)
This article presents a number of becomings in being-knowing-doing research at an Argentinian state university, in the event of their entanglement with certain heritage and recent onto epistemological options. Besides describing kinship and other family relationships, the text delves into their influence and has the intention of documenting some contemporary movements with the capacity to narrow the distances between the academia and “reality”, as ordinary people feel it. It focuses, thus, on the intercourse between criticalities and the decolonial turn with queer phenomenology, neomaterialismos and the posthumanisms/humusities, on the one hand, but also on some ordinary experiences that are defining new attention regimes. Instead of proving recipes or standardized solutions, the article seeks to leave open the question about the social value of research and universities, as well as their capacities to affect the presents. It is grounded on the belief that pedagogies may be lived as technologies to further de/re-educations that matter.
Keywords: research; ontoepistemis; kinship; affects/effects; becomings